BEYOND BEHAVIOR. - Black-Mitchell, Roshunda (Literacy Today (2411-7862))
The article focuses on the impact of trauma-informed education on understanding student behavior and supporting literacy development. Topics include the effects of adverse childhood experiences on learning, the connection between trauma and literacy challenges, and the importance of supportive classroom practices.